Examining the Effectiveness of Fear Appeals in Prompting Help‐Seeking: The Case of At‐Risk Gamblers. Issue 6 (June 2017) - De Vos, Svetlana; Crouch, Roberta; Quester, Pascale; Ilicic, Jasmina
ABSTRACT: With a sample of Australian at‐risk gamblers, this research examines the impact of gender and individual difference in experiential avoidance (EA; cognitive and emotional suppression) on the processing of fear appeals. Study 1, through thematic analysis, explores fear appeal perceptions among at‐risk gamblers. The results identify that relevant threats, such as social and psychological, should be integrated into fear‐inducing advertising stimuli. Study 2 uses multigroup comparisons in structural equation modeling (SEM) to test the robustness of the revised protection motivation model (RPMM) in predicting the effectiveness of fear appeals to induce help‐seeking intentions in at‐risk gamblers. This research examines the boundary conditions of the RPMM through the moderating roles of gender and EA. The results provide evidence that fear partially mediates the impact of perceived susceptibility (PS) on help‐seeking intentions in low experiential avoiders, whereas high experimental avoiders resist fear elicitation. Furthermore, evoked fear does not lead to help‐seeking intentions in male at‐risk gamblers. In female at‐risk gamblers, while fear prompts help‐seeking intentions, PS (i.e., probability of harm) does not translate to behavioral intentions via fear. For both genders and low and high experiential avoiders, cognitive appraisals of PS significantly and positively impact help‐seeking intentions. This research demonstrates the unique roles of gender and EA on fear appeal effectiveness in at‐risk gamblers.